Influence of oxygen concentration on the neuroprotective effect of hydrogen inhalation in a rat model of cardiac arrest - Wang, Jianjie; Shen, Yiming; Li, Jingru; Chen, Bihua; Yin, Changlin; Li, Yongqin (Frontiers in Neurology, 2022)
Background: Post-cardiac arrest brain injury is the main cause of death in patients resuscitated from cardiac arrest. Previous studies demonstrated that hydrogen inhalation mitigate post-cardiac arrest brain injury. However, factors affecting the efficacy of hydrogen remain unknown. In the present study, we investigated the influence of oxygen concentration and targeted temperature on neuroprotective effect in a cardiac arrest rat model of ventricular fibrillation (VF). Methods: Cardiopulmonary resuscitation (CPR) was initiated after 7 min of untreated VF in adult male Sprague-Dawley rats. Immediately following successful resuscitation, animals were randomized to be ventilated with 21% oxygen (21%O2), 2% hydrogen and 21% oxygen (2%H2+21%O2), 2% hydrogen and 50% oxygen (2%H2+50%O2), or 2% hydrogen and 98% oxygen (2%H2+98%O2) for 3 h. For each group, the target temperature was 37.5°C for half of the animals and was 35.0°C for the other half. Results: No statistical differences in baseline measurements and CPR characteristics were observed among groups. For animals with normothermia, 2%H2+50%O2 (123[369] vs. 500[393], p=0.041) and 2%H2+98%O2 (73[66] vs. 500[393], p=0.002) groups had significantly lower neurological deficit scores (NDS) at 96-h and significantly higher survival (75.0% vs. 37.5%, p=0.033 and 81.3% vs. 37.5%, p=0.012) than 21%O2 group. For animals with hypothermia, no statistical difference in NDS among groups but 2%H2+98%O2 has significantly higher survival than 21%O2 group (93.8% vs. 56.3%, p=0.014). Conclusions: In this cardiac arrest rat model, inhaling 2% hydrogen combined with high concentration of oxygen improved 96-h survival, either under normothermia or under hypothermia.